VISIBILIDADE E CRIMINALIDADE: UM ESTUDO SOBRE A APLICABILIDADE DE ISOVISTAS 2D, 3D E ANÁLISES GRÁFICAS DE VISIBILIDADE NA AVALIAÇÃO DE VULNERABILIDADE URBANA AO CRIME - Melo Junior, Sílvio Pereira Bezerra de; Silva, Robson Canuto da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study aims to investigate the applicability of 2D and 3D isovists, as well as Visibility Graph Analysis (VGA), for evaluating urban vulnerability to crime. The methodology is based on correlations between number of crime occurrences and: (1) measurements taken from 2D isovists (area, perimeter and occlusivity); (2) qualitative attributes of 3D isovists (more or less spatial cavities); and (3) mean values of visual integration (VGA). The 2D isovists were produced through the plugin DeCoding Spaces Toolbox for Grasshopper and the 3D isovists were generated by using algorithms within Rhinoceros 5.0 and Grasshopper 0.9.76.0. The VGA maps were elaborated within DepthmapX. For this study, were selected nine segments of Boa Viagem, located in Recife-PE, a neighbourhood which is known for high rates of robberies. These segments were defined based on number of crime occurrences: (1) above 10; (2) from 1 to 10; (3) no occurrence. Although the number of samples is reduced, the results suggest that criminals prefer much more spaces with low occlusivity. In order to facilitate crime, they choose less occlusive spaces so that they can have higher visual control of their victims.